Modificação das propriedades dos polímeros de NBR carboxilado comerciais a partir da incorporação de nanopartículas sintéticas - Sala, Renata Lang (2014)
Aiming to overcome the performance of polymers, a new class of hybrid materials has emerged by the fillers insertion into polymeric matrices. In this sense, silica nanoparticles with a diameter of 250 nm were modified by the silane agente, 3-(trimethoxysilyl)propyl methacrylate, and covered by a polymeric shell of styrene-divinylbenzene copolymer, in order to improve the silica dispersion in the carboxylated nitrile rubber (XNBR) and to understand the inorganic/organic interface. The nanocomposites were prepared by the colloidal route, dried and deployed as self-sustained films. Further, they were characterized by structural, morphological, thermical and dynamicalmechanical analysis. The surface modification of silica was effective and the thickness of polymeric shell was controlled by the time of the polymerization reaction and monomers concentration. The surfactant sodium dodecyl sulfate, used as nanoparticles dispersant, changed the thermal and mechanical performance of nanocomposites, since it probably remained organized in the polymer matrix. The nanocomposites showed to have interaction between their components, which may have been especially promoted by the carboxylate groups from XNBR, resulting in materials thermally more stables. The final materials presented a mass fractal system and the formation of coacervates, which resulted in similar thermal capacity of XNBR, lower loss and storage modulus, reduced tan δ and activation energy for the relaxation process, which are typical of materials that present good interfacial interaction between the inorganic nanoparticles and the polymeric matrix.